Like to Learn: Reimagining Instagram as Architecture Learning Platform - Redyantanu, Bramasta Putra (Journal of Architectural Research and Design Studies, 2025)
This study posits that Instagram extends beyond social networking, serving as a tool for informal learning and knowledge dissemination. Architecture, deeply intertwined with visual exploration, finds a natural ally in Instagram, a popular visual-based social media platform in Indonesia. This study is an exploratory qualitative study, attempting to reflect on the reinterpretation of Instagram as a potential medium for informal architecture learning. This case study explores Instagram's role in knowledge access for Indonesian architecture, examining its support for learning activities through users, content, and interaction. The findings highlight Instagram's potential to enhance architectural education in learning, especially through professional architects who share knowledge on the platform. Users on Instagram are both consumers and creators of content, fostering a dynamic exchange of ideas. Instagram’s features, like comments and live sessions, support a collaborative learning environment. Its visual focus suits architectural learning, helping students and professionals stay informed and engaged. Instagram's extensive reach and real-time interaction capabilities, independent of pre-existing personal connections, render it an invaluable tool for explorative knowledge dissemination. This suggests its potential to play a significant role in the future of architectural education. Keywords: Architecture; Digital; Instagram; Learning; Platform